The impact of global trends on ILDS. Issue 4 (11th November 2014) - Michael Baker, David; Posner, Beth
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this article surveys two recent library trend reports to identify key developments likely to impact how librarians, and particularly interlending and document supply (ILDS)/interlibrary loan (ILL) professionals, will facilitate the discovery and delivery of information in the future. Design/methodology/approach – Drawing on the New Media Consortium's "Horizon Report: Library Edition" (2014) and the recent discussion draft of the American Library Association Policy Revolution! Initiative's "Trends Report: Snapshots of a Turbulent World" (2014), this review essay illuminates major trends that will shape the future of information and library resource sharing. Findings – Global trends in technology, demographics, the economy, the environment and more will also effect the ability of librarians to facilitate the discovery and delivery of information. In some cases, these will lead to decreased need for traditional ILL. However, in others cases there will be an increased need as well as enhanced ability for librarians to connect people and information. Originality/value – Trend reports are popular in many areas, including the library world, as is predicting the future of libraries and ILDS. This article makes a new contribution by applying specific recent reports specifically to library discovery and delivery.